2015
DOI: 10.1523/jneurosci.1289-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Local Astrocyte Support Disrupts Action Potential Propagation and Glutamate Release Synchrony from Unmyelinated Hippocampal Axon Terminals In Vitro

Abstract: Neuron-astrocyte interactions are critical for proper CNS development and function. Astrocytes secrete factors that are pivotal for synaptic development and function, neuronal metabolism, and neuronal survival. Our understanding of this relationship, however, remains incomplete due to technical hurdles that have prevented the removal of astrocytes from neuronal circuits without changing other important conditions. Here we overcame this obstacle by growing solitary rat hippocampal neurons on microcultures that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…First, we found that inhibition of oxidative phosphorylation alone, rather than glycolysis alone, produced changes to sodium current and action potential waveform. Second, because hippocampal glutamate release is quite sensitive to changes in action potential waveform (Prakriya and Mennerick, 2000;Meeks and Mennerick, 2004;Sobieski et al, 2015;Lujan et al, 2016), if the somatic action potential waveform changes that we observed after oligo treatment alone were propagated to terminals, then we would have expected strong alteration of transmitter release. Instead, we found that the changes to excitability produced by oligo alone were not associated with deficits in evoked PSCs.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…First, we found that inhibition of oxidative phosphorylation alone, rather than glycolysis alone, produced changes to sodium current and action potential waveform. Second, because hippocampal glutamate release is quite sensitive to changes in action potential waveform (Prakriya and Mennerick, 2000;Meeks and Mennerick, 2004;Sobieski et al, 2015;Lujan et al, 2016), if the somatic action potential waveform changes that we observed after oligo treatment alone were propagated to terminals, then we would have expected strong alteration of transmitter release. Instead, we found that the changes to excitability produced by oligo alone were not associated with deficits in evoked PSCs.…”
Section: Discussionmentioning
confidence: 91%
“…7A), but many other facets of evoked transmission are intact (Sobieski et al, 2015). Recovery of EPSCs after the vesicle depletion challenge was slightly depressed in Ϫastrocyte neurons compared with ϩastrocyte neurons when recorded in control medium (Fig.…”
Section: Endogenous Monocarboxylate Powers Oxidative Phosphorylation mentioning
confidence: 88%
See 2 more Smart Citations
“…Hippocampal and cortical neurons were prepared from individual P0-P1 mouse pups using a modification of methods described for rat neuronal culture 21 . Mouse pups were genotyped after the fact to determine presence or absence of the MFN2*T105M transgene; neurons derived from mice lacking the transgene were designated as normal controls.…”
Section: Methodsmentioning
confidence: 99%